Mediation Effect of Marketing Mix Strategy on Supply and Demand Towards Marketing Performance - PAYANGAN, Otto Randa; SAHABUDDIN, Romansyah; GIRIKALLO, Adrianus S. (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).21, 2017)
The design of this study aimed to examine whether factors such as: supply, demand, and strategy promotional mix can affect the performance of tourism marketing in Sulawesi-South and located in the Municipality of Makassar, Tana Toraja, Wajo, Municipality of Pare-Pare and District Bulukumba, and time of execution carried out from September to December 2004. The population in this study is the "Foreign tourists and Travelers archipelago" which came in South Sulawesi, district and municipality which he visited to make use accidental sampling method as the sample collection method. The analytical method used to test the hypothesis of the research is Structural Equation Modeling (SEM). Hasi analysis shows that there is a variable mediating effect on the influence of marketing mix strategy between Supply and Demand for performance marketing.